2018
DOI: 10.2196/10173
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health to Maintain Continuity of Patient-Centered Care for Chronic Kidney Disease: Content Analysis of Apps

Abstract: BackgroundChronic kidney disease (CKD) is a global health problem with a high economic burden, which is particularly prevalent in Taiwan. Mobile health apps have been widely used to maintain continuity of patient care for various chronic diseases. To slow the progression of CKD, continuity of care is vital for patients’ self-management and cooperation with health care professionals. However, the literature provides a limited understanding of the use of mobile health apps to maintain continuity of patient-cente… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 53 publications
(59 reference statements)
3
17
0
Order By: Relevance
“…In addition, the findings of this study are also consistent with those of a previous study [ 42 ] in which limited apps were found to be available for patient dietary self-management (8.7% vs 9.0%). Despite different evaluation aspects, we agreed with the study conducted by Lee et al [ 61 ], which found that commercial renal apps had limited capability to support renal patient self-management.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, the findings of this study are also consistent with those of a previous study [ 42 ] in which limited apps were found to be available for patient dietary self-management (8.7% vs 9.0%). Despite different evaluation aspects, we agreed with the study conducted by Lee et al [ 61 ], which found that commercial renal apps had limited capability to support renal patient self-management.…”
Section: Discussionsupporting
confidence: 89%
“…Prior studies had been conducted to evaluate commercial renal apps designed for both renal patients and health care professionals. These include studies pertaining to diet apps for general kidney diseases [ 14 ] and health apps specific to CKD management [ 42 , 61 ]. In comparison, this study was focused on diet apps designed specifically for dietary self-management in the dialysis population.…”
Section: Discussionmentioning
confidence: 99%
“…There are only few available apps that target patients with CKD specifically; however, most of them are available on app stores, and information on their efficacy and usability are rather scarce [ 41 ]. A recent content analysis of mobile apps for CKD revealed that available apps fail to provide the continuity of patient-centered care that is needed to support patients with CKD [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 26 included articles, one reported a priori protocol registration 7 and four stated reporting was based on the PRISMA guideline for systematic reviews. 7,30,37,39 Adam 20 World of Urology Prostate Cancer Athilingam 21 JMIR Cardiology a Heart Failure Bhattarai 22 Pain Medicine Arthritic Pain Garcia-Cruz 23 Actas Urologicas Espanolas Men's sexual disorders Jupp 24 Pediatric Blood and cancer Cancer/Oncology Lee 25 JMIR mHealth and uHealth a Chronic Kidney Disease Luo 26 Journal of Clinical Rheumatology Rheumatoid Arthritis Rey 27 Neurologica Parkinson's Disease Svendsen 28 Journal of Dermatological Treatment Psoriasis Choi 29 Health Informatics Journal a Osteoarthritis Grainger 30 JMIR mHealth and uHealth a Rheumatoid Arthritis Martinez 31 JMIR Diabetes a Diabetes Rossi 32 mHealth a Diabetes Sobnath 33 JMIR mHealth and uHealth a Chronic Obstructive Pulmonary Disease Xie 34 JMIR mHealth and uHealth a Cardiovascular Disease Arnhold 35 JMIR a Diabetes Brouard 36 Annals of Medicine Cancer Brzan 37 Journal of Medical Systems a Diabetes Con 38 JMIR mHealth and uHealth a Inflammatory Bowel Disease Machado 7 Best Practice and Research Clinical Rheumatology Low back pain Fijacko 39 Journal of Medical Systems a Type 2 Diabetes Lee 40 British Journal of Sports Medicine Concussion Wurzer 41 Burns Burns Vega 42 PLOS One Pain Wallace 43 Journal of Opioid Management Chronic Pain El-Gayar 44 Journal of Diabetes Science and Technology Diabetes a Journals listed in field of 'Medical Informatics' in InCites Journal Citation Reports (Clarivate Analytics, 45 or published in subsidiary journal of JMIR.…”
Section: A Priori Review Registration and Registration Guidelinementioning
confidence: 99%